General Practitioners’ views of blood pressure control in people with and without dementia - van der Wardt, Veronika; Conroy, Simon; Taggar, Jaspal; Gladman, John R.F. (University of Nottingham, 2015)
Introduction: Since 2012, our group has undertaken a programme of research examining the treatment of hypertension in people with dementia. Hypertension is managed by GPs, who are guided by NICE guidelines, which make no mention of different management in people with dementia. We sought to explore the views of GPs on whether they manage hypertension differently in people with dementia. Method: We chose to try using an on-online survey to seek views, with both open and closed questions. We offered vignettes describing 71 and 83 year old women without cognitive impairment or with dementia, and a free text box – comments provided in this box were analysed thematically. Results: Although 427 GPs responded to the questionnaire, this was only 7% of all GPs eligible. Responding GPs were twice as likely not to offer treatment to the patient aged 71 with dementia and a BP above 140/90 (NICE threshold) compared to one without dementia (23.9% vs 11.7%). A similar finding was found when the vignettes involving 83 year old women with and without dementia (using 160/100, the NICE threshold for this age group) where 7.3% would not offer treatment in the woman with dementia compared to 3.3% in those without dementia. The analysis of free text identified four major themes, which were labelled as ‘complex decisions, ‘blood pressure measurement‘, ‘uncertainties around treatment’ and ‘compliance with guidelines’. Discussion: The low response rate in this survey makes the findings potentially unreliable, and other methods of ascertaining GP views, intentions or practices should be considered. Despite this, the findings from this study, in particular the free text comments indicate that the management of hypertension in people with dementia, is likely to be more complex than current guidelines indicate, and we propose that further research and clarification of best practice would be helpful.